Helping students into, through, and beyond: reading strategies for english-as-a-foreign-language students - Sandra Mano (Ilha do Desterro)
Reading and writing research indicates that students do both activities more successfully if the process that readers and writers engage in is consciously activated to aid in the production of products. In writing instruction, this has led to a focus on facilitating the composing process through the introduction of pre-writing, composing, revising, and editing activities. Currently the same types of strategies are available to facilitate the reading process. Many of these, developed by individual teachers or projects such as the California Literature Project, aim to help students read challenging materials in their first language.